1995
DOI: 10.1021/tx00050a006
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic Methylation of Arsenic Compounds: Assay, Partial Purification, and Properties of Arsenite Methyltransferase and Monomethylarsonic Acid Methyltransferase of Rabbit Liver

Abstract: A rapid, accurate, in vitro assay utilizing radioactive S-adenosylmethionine (SAM) has been developed for the methylation of arsenite and monomethylarsonate (MMA) by rabbit liver methyltransferases. The assay has been validated by separating, identifying, and measuring the products of the reaction using chloroform extraction, ion exchange chromatography, TLC, or HPLC. The enzymes involved in this pathway, arsenite methyltransferase and MMA methyltransferase, have been purified approximately 2000-fold from rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(108 citation statements)
references
References 34 publications
2
106
0
Order By: Relevance
“…These results are consistent with evidence that trivalent arsenicals are the preferred substrate for this enzyme and that the pentavalent arsenicals must be reduced enzymatically or nonenzymatically before methylation (7,11,41). Based on estimated molecular weights, the protein purified from rat liver cytosol (ϳ42.000) is probably not identical with the enzyme purified from rabbit liver cytosol (ϳ60,000) that catalyzes the methylation of arsenite and methylarsonous acid (10,11). S-Adenosyl-Lmethionine:arsenic(III) methyltransferase from rat liver differs kinetically from arsenic methyltransferases purified from rabbit or hamster liver cytosol.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These results are consistent with evidence that trivalent arsenicals are the preferred substrate for this enzyme and that the pentavalent arsenicals must be reduced enzymatically or nonenzymatically before methylation (7,11,41). Based on estimated molecular weights, the protein purified from rat liver cytosol (ϳ42.000) is probably not identical with the enzyme purified from rabbit liver cytosol (ϳ60,000) that catalyzes the methylation of arsenite and methylarsonous acid (10,11). S-Adenosyl-Lmethionine:arsenic(III) methyltransferase from rat liver differs kinetically from arsenic methyltransferases purified from rabbit or hamster liver cytosol.…”
Section: Discussionsupporting
confidence: 77%
“…A critical factor in the success of this purification scheme was inclusion of GSH and DTT in all buffers. Earlier work demonstrated that GSH was critical to the maintenance of arsenic methylating activity in an in vitro reaction system that contained rat liver cytosol (33,34) and that DTT promoted the dimethylation reaction catalyzed by the purified rabbit liver protein (10). S-Adenosyl-L-homocysteineSepharose affinity chromatography yielded a single Coomassie Blue staining band on SDS-PAGE (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In rats and hamsters, DMAs is further methylated to yield trimethylarsine oxide (TMAs V O) (Yamauchi and Yamamura, 1985;Yoshida et al, 1998). Two classes of enzymes are involved in the methylation of iAs, including As V -reductases (Gregus and Nemeti, 2002;Radabaugh et al, 2002;Zakharyan and Aposhian, 1999;Zakharyan et al, 2001) and As III -methyltransferases Zakharyan et al, 1995). The metabolic conversion of iAs is generally recognized to be a determinant of the toxic and carcinogenic effects of this metalloid.…”
Section: Introductionmentioning
confidence: 99%